The light we lost : a novel - Santopolo, Jill (New York : G.P. Putnam's Sons, 2018)
"Lucy is faced with a life-altering choice. But before she can make her decision, she must start her story--their story--at the very beginning. Lucy and Gabe meet as seniors at Columbia University on a day that changes both of their lives forever. Together, they decide they want their lives to mean something, to matter. When they meet again a year later, it seems fated--perhaps they'll find life's meaning in each other. But then Gabe becomes a photojournalist assigned to the Middle East and Lucy pursues a career in New York. What follows is a thirteen-year journey of dreams, desires, jealousies, betrayals, and, ultimately, of love ... Their journey will take Lucy and Gabe continents apart, but never out of each other's hearts. Was it fate that brought them together? Is it choice that has kept them away?"--Jacket.
Includes discussion guide and author interview.
Includes bibliographical references (pages 327-328).
Keywords: Man-woman relationships -- Fiction; Life change events -- Fiction; Fate and fatalism -- Fiction; Romance fiction; Romance fiction